UJI VALIDITAS MEDIA PAPUSTAS (PAPAN PUZZLE SISTEM TATA SURYA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Shevi Tias Anggita; Iis Daniati Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students’ ability to understand the solar system material is often hindered by its abstract nature and the limited use of concrete media in learning. This study aims to determine the validity level of Papustas (Solar System Puzzle Board) as a learning aid in IPAS (Natural and Social Sciences) subjects at the elementary school level. The media is designed to present celestial object concepts in a visual and interactive way through a puzzle game, thus enhancing students’ interest, comprehension, and active engagement. The research was conducted at UPT SDN Patihan 1 with 15 sixth-grade students as participants, using a research and development (R&D) approach with a descriptive quantitative method. Data were collected through interviews, observations, questionnaires, tests, and validation sheets. The validation process involved three experts: a content expert, a media expert, and a language expert. The results showed that Papustas received a score of 90% from the content expert, 94.7% from the media expert, and 86% from the language expert, with an average validity score of 90.23%. These results indicate that Papustas falls into the “very valid” category and is feasible to be used as a learning medium to help students understand solar system concepts more concretely, enjoyably, and meaningfully.